Unsteady Aerodynamics, Aeroacoustics and Aeroelasticity of Turbomachines - Hall, Kenneth C.; Kielb, Robert E.; Thomas, Jeffrey P. (Springer Netherlands : Imprint: Springer, 2006)
This textbook is a collection of technical papers that were presented at the 10th International Symposium on Unsteady Aerodynamics, Aeroacoustics, and Aeroelasticity of Turbomachines held September 8-11, 2003 at Duke University in Durham, North Carolina. The papers represent the latest in state of the art research in the areas of aeroacoustics, aerothermodynamics, computational methods, experimental testing related to flow instabilities, flutter, forced response, multistage, and rotor-stator effects for turbomachinery.